Pengaruh Pemberian Pakan Cacing Tanah (Lumbricus rubellus) dan Pelet Terhadap Pertumbuhan dan Perkembangan Benih Ikan Lele Dumbo (Clarias gariepinus) - Riko Irwanto; Novia Lesti (University of Bengkulu, 2021)
Catfish is a freshwater fish commodity that is currently being sought after by many people for consumption. The demand for catfish is increasing day by day. Catfish farming is one business that can develop rapidly. In the fish culture system, there are several factors such as fish growth. Factors that greatly affect the growth and development of fish are feed. The research objective was to determine the effect of different feeding on the growth and development of African catfish (Clarias gariepinus) and to determine the nutritional content of types of feed for African catfish (Clarias gariepinus). This research was conducted in Desa Tugang, Kelapa District, West Bangka Regency, Bangka Belitung Islands Province. The research was conducted by observing the growth of catfish seeds which included total length, total weight, height, head length, tail length and dorsal fin length. The development of catfish seeds observed was the activity of moving and eating feed for 3 weeks of maintenance. The results of the study were calculated using the absolute weight growth formula and the absolute length growth formula. The study design used a completely randomized design (CRD) using 2 variations of feed with 5 times of repetition. The data obtained were analyzed using analysis of variance (ANOVA), to determine whether or not the feed given was significant or not on the growth of catfish. The results showed that catfish seeds fed natural earthworms had a faster growth and better development rate compared to pellet-fed catfish seeds. The ANOVA test results different feeding showed a significant effect on total length growth weight, total weight, head length, and dorsal fin length (F count?F table). Meanwhile, height and tail length did not have a significant effect (F count < F table). Keywords: Growth, Development, Catfish, Feed.